Question:
For f(x) = 3x+1 and g(x) = x^2 - 6, find (f - g)(x)
O A. 3x² - 17
O B. x^2 – 3x-7
O C. -x^2+3x+7
O D. - x^2 + 3x - 5
Answer:
Option C
For f(x) = 3x+1 and g(x) = x^2 - 6 then the value of
![(f - g)(x) = - x^2 + 3x + 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ivvi88v9eg5ajxiesa9ru6di9dy32zpyv4.png)
Solution:
Given that,
![f(x) = 3x + 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nlhxo6t0a8vhzm9n45ekzt1qp0nx3ti5xu.png)
![g(x) = x^2 - 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8otldrp9z4i0hvdnwhgwqd03qdql8np6un.png)
To find: (f - g)(x)
We know that,
(f – g)(x) = f (x) – g(x)
Let us substitute the given values of f(x) and g(x) to find (f – g)(x)
![(f - g)(x) = 3x + 1 - (x^2 - 6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9hhpoe2einciof9fedl8zndm7jt5u796cn.png)
On multiplying the negative sign with terms inside second bracket
![(f - g)(x) = 3x + 1 - x^2 + 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/holzijrtq44kjdn0ko5st2v5ucm1n4zilk.png)
![(f - g)(x) = 3x - x^2 + 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eksipy1anpdv3z3pgii2zalumgd3l1vqb6.png)
On rearranging the terms we get,
![(f - g)(x) = - x^2 + 3x + 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ivvi88v9eg5ajxiesa9ru6di9dy32zpyv4.png)
Thus the value of (f - g)(x) is found out and option C is correct